LEARNING ENGLISH AS ADDITIONAL LESSON TROUGH LOCAL CULTURE - Arif Ma'mun Rifa'i (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2016)
This paper aims to describe how local culture used in learning English as additional foreign language lesson, at least learners’ culture can be dominantly occupied in foreign language learning better than foreign language culture. However, culture is too intimately bound up with language thus cannot be separated each other. Learning foreign language by influencing local cultural after all is not easy it also will be demanding to teacher’s ability in both cultures.Several issues which occur in language teaching, especially foreign languages include anything related to the culture, the problem is a foreign culture sometimes less is acceptable in learners’ culture, some expressions sometimes cannot be completely absorbed because students have a different background that form their understanding and culture all of them is influenced by social, cultural, and religious. The gap between cultures is inevitable namely origin language culture with the culture of language learners. Recognition of the cultural differences are certainly not necessarily to dichotomize those differences but rather on integrating both, in terms of integrating the culture cannot be denied that this is a difficult but the important thing to be concerned during the application of the language can be directed to the local culture then this will be very helpful using examples of student culture in which they live than helping them, it would also help preservation of local cultures to be exist.